PERLINDUNGAN HAK CIPTA SISTEM OPERASI KOMPUTER DENGAN LISENSI GPL “GENERAL PUBLIC LICENSE” BERDASARKAN UU HAK CIPTA INDONESIA: Copyright Protection Of Computer Programs With The Gpl "General Public License" Under The Indonesian Copyright Law - Devlin Ianindra Putra; Rakhmita Desmayanti (Reformasi Hukum Trisakti, 2024)
Copyright is a creation related to art, literature and science which is regulated in Law no. 28 of 2014 concerning Copyright. Technological developments are driven by the rapid development of science, which has resulted in many innovations, thus encouraging the regulation of copyright on computer programs. The formulation of the problem in the research is Can an Operating System with a GPL license be protected by the Copyright Law in Indonesia? And what are the provisions for moral rights and economic rights in an Operating System with a GPL license.This research was conducted by the research method of library, a type of normative juridical research with descriptive research properties with conclusions drawn with deductive logic. Results and conclusions about operating system with GPL license makes all able to modify the operating system in accordance with the freedoms where there is permission to modify by another user is regulated in the GPL license agreement and has automatic protection according to the law, even if there violation of economic rights, then the creator is entitled to make legal efforts.